2013
DOI: 10.1155/2013/685317
|View full text |Cite
|
Sign up to set email alerts
|

Local Overexpression of Interleukin-11 in the Central Nervous System Limits Demyelination and Enhances Remyelination

Abstract: Demyelination is one of the pathological hallmarks of multiple sclerosis (MS). To date, no therapy is available which directly potentiates endogenous remyelination. Interleukin-11 (IL-11), a member of the gp130 family of cytokines, is upregulated in MS lesions. Systemic IL-11 treatment was shown to ameliorate clinical symptoms in experimental autoimmune encephalomyelitis (EAE), an animal model of MS. IL-11 modulates immune cells and protects oligodendrocytes in vitro. In this study, the cuprizone-induced demye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 38 publications
0
31
1
Order By: Relevance
“…More recently, it was shown that overexpression of IL-11 in the brain reduces the extent of demyelination and enhances remyelination in the cuprizone-induced demyelinating disease model [57]. We did not observe histologic evidence of more severe demyelination in IL-11Rα −/− mice during EAE.…”
Section: Discussioncontrasting
confidence: 70%
“…More recently, it was shown that overexpression of IL-11 in the brain reduces the extent of demyelination and enhances remyelination in the cuprizone-induced demyelinating disease model [57]. We did not observe histologic evidence of more severe demyelination in IL-11Rα −/− mice during EAE.…”
Section: Discussioncontrasting
confidence: 70%
“…Moreover, it was reported that deletion of Ccl3 gene caused a delay of neuronal loss in Sandhoff mice (Hexb-/-Mip1α-/-mice) by inhibiting macrophage infiltration to the inflammatory sites, which resulted in improved neurologic status and a longer lifespan (Wu and Proia 2004). Additionally, Hexb-/-Tnfα-/-mice resulted in a delayed neurodegenerative cascade by an extending lifespan, improving sensorimotor coordination, decreasing levels of astrogliosis and neuronal cell death [53]. We suggest that adding antagonists of pro-inflammatory cytokines and chemokines such as Ccl3 or Ccl4 in daily feeding of Hexa-/-Neu3-/mice may reverse neuroinflammatory conditions.…”
Section: Discussionmentioning
confidence: 89%
“…We next examined levels of IL‐11, an anti‐inflammatory cytokine with known immunomodulatory and neuroprotective properties (Maheshwari et al, ; Trepicchio and Dorner, ; Trepicchio et al, ; Zhang et al, ). Semiquantitative RT‐PCR measurement of IL‐11 mRNA revealed an increase in IL‐11 expression, as well as an expected reduction in TNFα expression in EE versus NE brains (Fig.…”
Section: Discussionmentioning
confidence: 99%